1995
DOI: 10.1111/j.1476-5381.1995.tb15950.x
|View full text |Cite
|
Sign up to set email alerts
|

The promotion of patent airways and inhibition of antigen‐induced bronchial obstruction by endogenous nitric oxide

Abstract: 1 The aim of the present study was to investigate the role of nitric oxide (NO), histamine and leukotrienes in bronchial obstruction. For this, guinea-pigs immunised against ovalbumin were studied under anaesthesia during challenge with antigen or agonists. 2 Challenge with nebulised antigen (0.1-1 mg) elicited dose-dependent increases in insuflation pressure which were abolished by combined administration of histamine and leukotriene antagonists. 3 Challenge with nebulised antigen (0.1-mg) also elicited dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…Intravenous administration of NOS inhibitors has also been applied in studies on the guinea-pig [9]. In the present study i.v.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intravenous administration of NOS inhibitors has also been applied in studies on the guinea-pig [9]. In the present study i.v.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute allergic reaction, endogenous NO has been suggested to play a protective role; this is indicated by small-animal studies, performed on guinea-pigs, which show that inhibition of NO production with NOS inhibitors increases airway responsiveness to allergen and histamine challenge [9,10]. The mechanisms for this have not been pinpointed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to eNOS it has also been postulated that in mice nNOS could have a role in promoting airway hyperresponsiveness (74,75). Different groups of investigators have shown that acute bronchoconstriction induced by allergen inhalation is potentiated by NOS inhibitors in sensitized guinea pigs in vivo, suggesting a modulation by endogenous protective NO on early asthmatic reaction in animal model (286,342,343). Other in vivo studies in guinea pigs have shown that the enhanced airway reactivity induced by allergen (6 h after exposure) is not further potentiated by pretreatment with NOS inhibitors (393,394) and that virus-induced airway reactivity is completely blocked by low doses of inhaled L-arginine (112), suggesting that allergenor virus-induced airway hyperreactivity is due to the impairment of endogenous release of protective NO.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…In the pulmonary circulation nitric oxide contributes to maintain the low pulmonary vascular resistance and modulates hypoxic pulmonary vasoconstriction (Archer et al 1989;Persson et al 1990;Stamler et al 1994). Other suggested functions for nitric oxide in the lung are host defence (Gustafsson et al 1991;Wei et al 1995), antiobstructive airway relaxation (Persson et al 1995a), ciliary activation (Jain et al 1993), and antioxidative function (Kavanagh et al 1994;Gustafsson 1996).…”
mentioning
confidence: 99%